The Role Of Land Deed Officials In The Conversion Of Agriculture Land Fucntion Related Land Social Function In Sragen Regency - Sri Prihartini; Yuliantoro Yuliantoro; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study aims to analyze the role, constraints and solutions of Land Deed Officials in the conversion of agricultural land related to social functions on land in Sragen Regency. In case conversion of agricultural land is associated with social functions on land, cannot be avoided, especially if the land is for a highway development project as is the case in Sragen Regency which also involves the role of Land Deed Officials. The role of Land Deed Officials in the conversion of agricultural land to highway development projects carried out within the period of 2014-2015 is the provision of consultation to the community included in the authority of PPAT. Thus, Land Deed Officials can provide assistance in managing the conversion of agricultural land to the community. Meanwhile, in the conversion of agricultural land for highway construction, there is no significant obstacle because the Land Deed Officials manages the transfer of agricultural land functions according to procedures set by the Regulation of the Head of the National Land Agency Number 2 year 2011 concerning Guidelines for Land Technical Considerations in Issuance of Location Permits, Determination Location, and Permission to Change Land Use. Thus, if in handling the conversion of agricultural land is in accordance with the provisions of existing regulations, the Land Deed Officials will be able to overcome the existing obstacles.Keywords: Role of Land Deed Officials; Conversion of Agricultural Land Function; Land Social Function